1969
DOI: 10.1136/pgmj.45.523.307
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for distinguishing normal and subnormal adrenocortical function using the Synacthen test

Abstract: SummaryThe Synacthen test consists of the measurement of plasma corticosteroid concentrations by a fluorimetric method before (basal) and 30 min after a single intramuscular administration of 250 Vg of tetracosactrin (Synacthen), a synthetic polypeptide with ACTH activity equivalent to that of natural corticotrophin.In a control group of forty-five subjects the basal plasma corticosteroid level was not lower than 6 tig/ 100 ml (a lower limit of 5 ,tg/100 ml is accepted in the afternoon and evening), the increm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Adrenal function was tested in these three studies, and no significant impairment of adrenal function was detected on increasing the d\ose to 800 gg daily. Although Gaddie et al (1973) noted a smaller incremental increase in the response to a tetracosactrin challenge at 1600 tg daily, the test was well within the defined normal limits (Greig et al, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…Adrenal function was tested in these three studies, and no significant impairment of adrenal function was detected on increasing the d\ose to 800 gg daily. Although Gaddie et al (1973) noted a smaller incremental increase in the response to a tetracosactrin challenge at 1600 tg daily, the test was well within the defined normal limits (Greig et al, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…Our two cases had low or low normal cortisol level and increased ACTH, and had a subnormal response to rapid ACTH test. There has been controversy about the criteria for normal adrenal function in rapid ACTH test [3,5,6]. It was earlier reported that the basal plasma corticosteroid concentration, measured by fluorimetric assay, is not less than 6 ,ug/dl, the increase is not less than 7 ,ag/dl, and the concentration following stimulation is not less than 18 jig/dl ("6, 7, 18 rule") [5].…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy about the criteria for normal adrenal function in rapid ACTH test [3,5,6]. It was earlier reported that the basal plasma corticosteroid concentration, measured by fluorimetric assay, is not less than 6 ,ug/dl, the increase is not less than 7 ,ag/dl, and the concentration following stimulation is not less than 18 jig/dl ("6, 7, 18 rule") [5]. Other authors suggested that a peak cortisol concentration should be greater than or equal to 20 µg/dl [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…15,16,17 For this reason, in stress, the evaluation of appropriateness of the activation of the HPA axis requires dynamic testing. Adrenal insufficiency is diagnosed when on stimulation test the peak serum cortisol is <500 nmol/L (18 µg/dL), 18 alternatively it has been proposed that increment during ACTH stimulation test <250 nmol/L (9 µg/dL) or basal cortisol <83 nmol/L (3 µg/dL) can be considered as diagnostic of AI. 18,19 Diagnostic evaluation of suspected cases of adrenal insufficiency is hindered by non-availability of injection Synacthen.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal insufficiency is diagnosed when on stimulation test the peak serum cortisol is <500 nmol/L (18 µg/dL), 18 alternatively it has been proposed that increment during ACTH stimulation test <250 nmol/L (9 µg/dL) or basal cortisol <83 nmol/L (3 µg/dL) can be considered as diagnostic of AI. 18,19 Diagnostic evaluation of suspected cases of adrenal insufficiency is hindered by non-availability of injection Synacthen. To overcome this limitation, we used Acton Prolongatum (Corticotrophin Carboxymethyl cellulose) as intramuscular ACTH stimulation test.…”
Section: Discussionmentioning
confidence: 99%